Molecular Cardiology in Clinical Practice - Sanders, Michael.; Kostis, John B. (Basic Science for the Cardiologist, 1999)
Cardiology is an area of great recent triumphs in pharmacological and surgical treatment, yet cardiovascular disease remains the leading cause of death and disability in the industrialized world. Coronary disease, heart failure, stroke and sudden arrhythmic cardiac death challenge both medical practitioners and scientists. With the dawning of the new `molecular' era, there is an awakened hope that a more fundamental understanding of biologic processes may eventually lead to new progress in the prevention and treatment of these persistent and seemingly intransigent problems. Molecular Cardiology in Clinical Practice brings together an outstanding panel of experts in cardiovascular disease who have been at the forefront of the application of molecular medicine to cardiology. Its intent is to help bridge the gap between modern medical practice and modern science, in the belief that an understanding of basic principles can lead to new insight into the problems of cardiac patients.